The State of the World's Children 1998 Focus on Nutrition - Bellamy, Carol; United Nations Children's Fund, New York, NY. ([S.l.] : Distributed by ERIC Clearinghouse, 1998)
This report on the well-being of the world's children focuses on the issue of malnutrition and its impact on children's lives. Chapter 1: (1) discusses the incidence of malnutrition and the complex interplay of factors that cause malnutrition, including poor health services and discrimination against women; (2) presents several approaches to ameliorating malnutrition, including community involvement, food fortification, growth monitoring and promotion, and supplementation programs; and (3) spotlights some of the scientific breakthroughs reducing malnutrition. Chapter 2 provides statistics related to basic indicators for nutrition, health, education, demographics, economic indicators and the situation of women, rates of progress, and regional summaries for 193 countries (listed alphabetically). It also lists countries in descending order of their estimated 1996 under-5 mortality rates. Included throughout the report are panel sections highlighting specific nutrition programs or scientific findings. Seven "Spotlights" feature information on the World Food Summit, breastfeeding, and several nutrients. (Contains approximately 68 references). (KB)
Availability: UNICEF, UNICEF House, 3 UN Plaza, New York, NY 10017; World Wide Web: http:// www.unicef.org; e-mail: pubdoc@unicef.org.
ERIC Note: For 1997 report, see ED 407 108; for 1997 summary report, see ED 407 109.
Microfiche.
mizan
Keywords: Child Health; Childhood Needs; Children; Developed Nations; Developing Nations; Foreign Countries; Hunger; Nutrition; Poverty; Statistical Surveys; Well Being; Indicators -- UNICEF -- United Nations Convention on Rights of the Child -- World Summit for Children 1990